Bambusuril analogs based on alternating glycoluril and xylylene units - Lízal, Tomáš (Beilstein J Org Chem, 2019)
The glycoluril monomer is a popular building block in supramolecular chemistry as it is used for the synthesis of versatile host molecules which can interact with cationic, anionic or neutral guest molecules. Here we present the design and synthesis of a new hybrid macrocycle containing glycoluril and aromatic units. The reaction afforded a mixture of macrocyclic homologues from which a two-membered macrocycle was isolated as the main product. Two disastereomers of the macrocycle were separated and characterized by means of NMR spectroscopy and X-ray crystallography. Conformational changes of these diastereomers were investigated using DFT models and variable-temperature NMR.